Legal Assistance For Micro, Small And Medium Enterprises Of Taro Chips In Tambakan Village,Blitar Regency, East Java Indonesia - Hervina Puspitosari; Lilik Suprianti; Alfian Chandra Ayuswantana (International Journal Of Community Service, 2021)
The importance of community empowerment and assistance in improving the quality of Human Resources, including infrastructure facilities to support business activities. MSMEs are a great opportunity to develop businesses, especially during the Covid 19 pandemic where there are many layoffs or a decrease in labor wages. Creative ideas, as well as expertise and skill, are very important in developing MSMEs. Chips are very practical because they are dry so they are more durable and easy to serve anytime. Chips are one type of snack product that is widely consumed and favored by the community so that it becomes a great opportunity in developing a taro chips business, one of which has great potential in earning income and improving the welfare of the people of Tambakan village, Blitar Regency. Through legality assistance activities, it is hoped that the community can start processing Home Industry Food Production Permits (PIRT). The legality of taro chips SMEs business actors can certainly increase their productivity because consumers feel safe with the products they consume so that it fosters consumer confidence which in turn can increase consumer purchasing power and is expected to be marketed outside the region. The taro chips product developed by partners that were previously only marketed in local villages with permits and existing brands is expected to continue to grow and increase the income of the local village community